Tallapoosa Cane (Arundinaria alabamensis), a new species of temperate bamboo (Poaceae: Bambusoideae) from East Central Alabama - Triplett, J.k. (Phytotaxa, 2023)
Arundinaria alabamensis (Tallapoosa Cane) is described as a new species of North American temperate woody bamboo. Recognition of this species is consistent with molecular genetic data that suggests an origin through hybridization and subsequent diversification, as it bears a unique chloroplast DNA haplotype most similar to A. gigantea (River Cane), nuclear DNA haplotypes that cluster with A. appalachiana (Hill Cane) and A. tecta (Switch Cane), and a distinct AFLP fingerprint. Tallapoosa Cane can be distinguished from the other North American Arundinaria by a combination of vegetative characters including larger leaf size, foliage sheath pubescence, and a distinctive branch complement. This Alabama endemic is currently known from eight populations across four counties: Cleburne (3), Lee (3), Macon (1), and Randolph (1). The new species is described and compared with the related species of Arundinaria, and an identification key is included along with a comparative table based on morphological characters.